Japan's wooden heritage a journey through a thousand years of architecture - Fujimori, Terunobu 1946-; Fujitsuka, Mitsumasa 1939- (Japan library (Shuppan Bunka Sangyo Shinko Zaidan))
"Japan's Wooden Heritage: A Journey Through a Thousand Years of Architecture brings together essays by architectural historian Terunobu Fujimori and photographs by Mitsumasa Fujitsuka, and commentary by structural engineer Mikio Koshihara that originally appeared in Kateigah?o, Japan's premier magazine of art and culture, supplemented with additional essays by Mitsumasa Fujitsuka. What distinguishes this volume is its selection of 23 locations--including well-known temples and shrines but also lesser-known structures--to represent a broad scope of architectural styles, functions, and time periods; the outstanding photographs; and the distinct approaches taken by each of the three essayists"--Publisher's description.